2021
DOI: 10.1039/d0np00024h
|View full text |Cite
|
Sign up to set email alerts
|

Rocaglamide and silvestrol: a long story from anti-tumor to anti-coronavirus compounds

Abstract: The flavagline silvestrol is a potential candidate against viral infections including COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…Among the host factors known to be required for the replication of a broad-spectrum of viruses, eIF4A stands out as one of the most promising targets. Additionally, rocaglates are increasingly being recognized as some of the most promising broad-spectrum antiviral compounds modulating the activity of eIF4A [ 24 , 93 ]. However, the development of such compounds, from basic and preclinical research to clinical studies and commercialization, involves a number of experimental, monetary, clinical, manufacturing, and regulatory challenges.…”
Section: A Pan-antiviral Translational Roadmap For Rocaglatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the host factors known to be required for the replication of a broad-spectrum of viruses, eIF4A stands out as one of the most promising targets. Additionally, rocaglates are increasingly being recognized as some of the most promising broad-spectrum antiviral compounds modulating the activity of eIF4A [ 24 , 93 ]. However, the development of such compounds, from basic and preclinical research to clinical studies and commercialization, involves a number of experimental, monetary, clinical, manufacturing, and regulatory challenges.…”
Section: A Pan-antiviral Translational Roadmap For Rocaglatesmentioning
confidence: 99%
“…Recent advances in the development of compounds to target the cellular, cap-dependent DEAD-box RNA helicase eIF4A, an essential factor in viral protein synthesis, have underscored the potential of targeting this translational host factor as an antiviral strategy [ 24 ]. A large number of RNA viruses depend on eIF4A to translate their mRNAs because the complex structure of their 5′ untranslated regions (5′UTRs) requires the helicase activity of eIF4A to form the 43S-preinitiation complex (43S-PIC) during translation initiation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the host factors known to be required for the replication of a broad-spectrum of viruses, eIF4A stands out as one of the most promising targets. Also, rocaglates are increasingly being recognized as some of the most promising broad-spectrum antiviral compounds modulating the activity of eIF4A [20,103]. However, the development of such compounds, from basic and preclinical research to clinical studies and commercialization, involves a number of experimental, monetary, clinical, manufacturing and regulatory challenges.…”
Section: A Pan-antiviral Translational Roadmap For Rocaglatesmentioning
confidence: 99%
“…Recent advances in the development of compounds to target the cellular, cap-dependent DEAD-box RNA helicase eIF4A, an essential factor in viral protein synthesis, have underscored the potential of targeting this translational host factor as an antiviral strategy [20]. A large number of RNA viruses depend on eIF4A to translate their mRNAs because the complex structure of their 5'-untranslated regions (5'UTRs) requires the helicase activity of eIF4A to form the 43S-preinitiation complex (43S-PIC) during translation initiation [21].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, apart from ongoing screenings for insecticidal properties, there has also been a great parallel interest in that class of compounds as potential anticancer agents (Ohse et al 1996;Wu et al 1997;Cui et al 1997;Lee et al 1998;Bohnenstengel et al 1999a,b;Wang and Duh 2001;Hausott et al 2004;Mi et al 2006a;Zhu et al 2007Zhu et al , 2009Cencic et al 2009;Ribeiro et al 2012;Basmadjian et al 2013). Moreover, anti-inflammatory (Baumann et al 2002;Proksch et al 2005;Fahrig et al 2005;Salim et al 2007b), antiprotozoal (Phongmaykin et al 2011;Astelbauer et al 2011Astelbauer et al , 2012Langlais et al 2018;Drinić et al 2019), and more recently, antiviral activities (Biedenkopf et al 2017;Müller et al 2018Müller et al , 2020Müller et al , 2021Todt et al 2018;Glitscher et al 2018;Elgner et al 2018;Henss et al 2018;Schulz et al 2021;Taroncher-Oldenburg et al 2021) were also reported which greatly stimulated further research in this class of compounds.…”
Section: Introductionmentioning
confidence: 99%